Cassava breeding and agronomy research in Malaysia during the past 15 years - Tan, Swee Lian (International Center for Tropical Agriculture, 2001)
The paper reviews cassava breeding and agronomy research carried out by MARDI over the 15-year period, 1984-1999. Evaluation of seedling clones derived from sexual seeds introduced from CIAT/Colombia and the Thai-CIAT program has culminated in the release of two varieties: Perintis (in 1988), which is a very high-yielding variety, and MM 92 (in 1992), which is a six-month variety; both varieties are widely adaptable. The shortcoming of both varieties is their rather low root starch contents compared to the local commercial starch variety, Black Twig. In the pipeline are two new clones: one with potential as a table variety, having low root cyanide content and showing suitability for making oil-fried crisps, a popular snack; the other, having a higher root yield than Black Twig while having a similar starch content. Agronomy research has given attention to: (a) reduction of production costs, (b) maximization of profits, and (c) expansion of cassava production into marginal areas. Strategies to reduce costs include the use of machines in field operations to reduce labor requirements, especially for planting and harvesting; development of a computer software package to diagnose major nutrient insufficiencies and to recommend fertilizer rates instead of using blanket fertilizer rates; decreasing the fertilizer recommendations and frequency of application when growing the early variety MM 92 on drained peat. In order to maximize profits, intercropping with sweet corn and the recycling of starch factory solid wastes as a supplementary fertilizer are advocated. With difficulties in accessing arable land for planting cassava, drained peat was found to be a potential area provided that specific agronomic practices are adopted. Likewise, planting on slopes requires the adoption of certain cultural practices, like the planting of contour grass barriers, to minimize soil erosion and sustain root yields.